Lexico-Semantic and Structural Transformations of Biblical Text when Translated Into Ossetian Language - L. B. Morgoeva (Научный диалог)
The article is devoted to the analysis of options for translating the Bible into the Ossetian language, taking into account the specifics of constructing sacred texts. The issues of interpretation of realities, compound names, structurally formed integral units in translation into a language that has a conceptual structure different from other languages and its own systemic organization are considered. It is noted that this is of great importance both for studying the actual translation of biblical texts, compiling a dictionary of religious terms and naming units, and for studying the full potential of linguistic possibilities in representing various kinds of complex realities with national and cultural specifics unusual for the Ossetian language, which determines the relevance of this work. The material was the Synodal translation of the Bible and versions of its translation into the ssetian language, the comparison of which made it possible to identify a number of features, the most consistent of which is the transliteration/transcription of compound names and onomastic terms. It is shown that traditional methods of translation do not always adequately reflect the meaning of the source text, as well as the method of rethinking can distort it beyond recognition, so a clear understanding of the lexical compatibility options of the target language units and the boundaries of their semantic range is necessary.